Fibroblast growth factor receptor inhibitors in glioma: a narrative review of recent advances - Han, Mingyu; Zhou, Zhaokai; Qian, Bi; Zhang, Qiyuan; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2026)
Gliomas are devastating CNS malignancies characterized by extreme molecular heterogeneity and poor prognosis; the fibroblast growth factor receptor (FGFR) signaling axis, which drives proliferation, stemness, and metabolic adaptation, has thus emerged as a crucial therapeutic target. This review systematically synthesizes recent advances in understanding FGFR dysregulation, the clinical application of FGFR inhibitors, and the overriding pharmacological hurdles to achieving effective CNS exposure. FGFR signaling is dysregulated in gliomas by a range of genomic alterations, including mutations, amplifications, and key oncogenic fusions (e.g., FGFR3-TACC3). Moreover, contemporary investigations have demonstrated that novel structural changes in FGFR2 and FGFR3 are frequently linked to an aggressive tumor biology and specific gene expression signatures, thus validating their function as powerful, clinically actionable drivers. Pharmacologically, dedicated inhibitors like Infigratinib have demonstrated anti-tumor activity in clinical Phase II trials for FGFR-altered recurrent gliomas, while the multi-kinase inhibitor Regorafenib has shown a modest survival benefit in recurrent GBM; however, mechanistic studies indicate that effective response often relies on co-targeting bypass pathways (e.g., CLK2) and mitigating the tumor’s metabolic dependency. Crucially, limited drug exposure through the blood-brain barrier (BBB) continues to be the foremost challenge, dictating optimization efforts toward compounds with favorable pharmacokinetic properties and novel delivery platforms, such as the covalent inhibitor futibatinib and liposomal formulations, to enhance brain penetrance. In conclusion, the evolving molecular landscape validates FGFR alterations as a targetable niche in gliomas, and future success depends critically on integrating comprehensive next-generation sequencing to identify aggressive FGFR variants, developing next-generation inhibitors with superior BBB permeability, and implementing rational combination strategies to achieve durable clinical benefit.